Kehujahan Hadis Ahad Menurut Mazhab Suni dan Syi’ah - M. Nasri Hamang (AL-Fikr, 2010)
This article discusses the position of ahad hadis according to both Sunni and Shi’i scholars. As being commonly acknowledge by muslims that Sunni school strongly holds an transmitted materials (riwayat) and opinions of all scholars among the prophet’s companions, while Shi’i school based its reason on merely materials and opinions from ahlu bait companions. Both schools actually have the same conclusion on the possibility to use ahad hadis as a source in Islamic law, but a few issues on transmission requirements. Both Sunni and Shi’i agree that ahad hadis is applicable to ibadah (worship), but not to akidah (faith) Shi’i school in particular requires the transmitter of ahad hadis school be ma’sum (devirely protected).